Resistance training and Down Syndrome: A narrative review on considerations for exercise prescription and safety - Melo, Geiziane Leite Rodrigues; Neto, Ivo Vieira de Sousa; Fonseca, Eduardo Fernandes da; Stone, Whitley; Nascimento, Dahan da Cunha (Frontiers in Physiology, 2022)
The current manuscript reviews the literature on the health effects of resistance training (RT) for individuals with Down syndrome (DS), focusing on this training modality's methodology, application, and safety. The literature has mentioned that early aging in this population is associated with loss of muscle strength, lower lean and bone mass, and increased obesity. It is necessary to propose non-pharmacological measures for prevention and health promotion. Thus, this review suggests a current research-based RT guide for individuals with DS. This review is divided into five sections: Section 1 briefly reviews DS and the effects on structural and functional decline and how exercise and physical activity can influence health aspects in this population; Section 2 summarizes the evidence for RT prescription; Section 3 briefly reviews the health and potential benefits of RT in individuals with DS. The findings from this review suggest that most individuals with DS should engage in moderate-intensity RT at least two days a week and perform RT on the major muscle groups and include balance training. The RT program should be modified and adapted according to individuals' characteristics and limitations. RT promotes positive, health-related benefits such as increasing strength, improving body composition, improving functional capacity and balance, reducing inflammatory status and oxidative stress, and improving the immune system. The RT protocols summarized in this current review provide guidance, critical conclusions, and novel research settings, which could be useful to coaches, clinicians, and researchers to effectively design RT program for individuals with DS.